In Search of Stupidity: Over 20 Years of High-Tech Marketing Disasters - Chapman, Merrill R. (Apress, 2012)
In 1982, Harper & Row published In Search of Excellence: Lessons from America's Best-Run Companies by Thomas J. Peters and Robert H. Waterman, Jr. In Search of Excellence quickly became a seminal work in the category of business management books and made its authors millionaires. Although it's no longer the literary obsession of freshly minted MBAs that it was back in the 1980s, the book's distribution and influence has proved long lasting and pervasive. After its introduction, the book stayed on best-seller lists for almost 4 years and sold over 3 million copies. A survey by WorldCat, an electronic catalog of materials from libraries in the United States and other countries, ranks In Search of Excellence as being on more library shelves than any other book in the world. With 3,971 libraries listing it as being in their collections, the book tops the list of 100 books held by libraries. It has held the number one position since 1989.